2013
DOI: 10.1111/liv.12291
|View full text |Cite
|
Sign up to set email alerts
|

Taurine‐induced insulin signalling improvement of obese malnourished mice is associated with redox balance and protein phosphatases activity modulation

Abstract: Our data provide evidence for an association between TAU-induced improved glycaemic control because of PTEN inactivation and higher AKT phosphorylation. These effects seem to be related with altered hepatic redox balance in obese mice, and this effect is impaired by protein malnutrition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
21
1
5

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 42 publications
3
21
1
5
Order By: Relevance
“…In our study, rats fed a LP diet showed lower body weight and similar biochemical parameters as in several other studies [7,8,54,55], demonstrating that these rats were a suitable model. Although insulinemia was reduced, glycemia was unchanged in rats fed either a LP or NP diet.…”
Section: Discussionsupporting
confidence: 82%
“…In our study, rats fed a LP diet showed lower body weight and similar biochemical parameters as in several other studies [7,8,54,55], demonstrating that these rats were a suitable model. Although insulinemia was reduced, glycemia was unchanged in rats fed either a LP or NP diet.…”
Section: Discussionsupporting
confidence: 82%
“…Tau also reduced superoxide production in the mitochondria of cardiomyocytes by enhancing electron transport chain activity (Jong et al 2012). Protein-restricted mice supplemented with Tau showed better redox balance and a reduction in ER stress markers such as p-PERK and BIP (Batista et al 2013a, b;Cappelli et al 2013). In accordance with all these studies, we herein report that Tau supplementation decreased the fold change in genes related to the unfolded protein response, apoptosis, and the ER stress pathway in the hypothalamus of the RHT and CHT mice (Tables 5, 6), which may contribute to better leptin signaling in these groups.…”
Section: Discussionmentioning
confidence: 98%
“…Recent studies from our group have demonstrated that Tau supplementation in obese mice induced by an HFD improves glucose tolerance and insulin sensitivity, which are impaired by obesity Camargo et al 2013 ;Cappelli et al 2014 ;Vettorazzi et al 2014 ). This improvement can be explained by a decrease in insulin hypersecretion (Vettorazzi et al 2014 ;Ribeiro et al 2012 ) and an increase in hepatic and muscle AKT phosphorylation Ribeiro et al 2012 ) seen in obese mice fed a HFD.…”
Section: Discussionmentioning
confidence: 79%